Response to Propoxyphene Market Withdrawal: Analgesic Substitutes, Doses, and Adverse Events. Issue 1 (January 2020) - Jeffery, Molly M.; Morden, Nancy E.; Larochelle, Marc; Shah, Nilay D.; Hooten, W. Michael; Meara, Ellen
Abstract : Objective: Experts cautioned that patients affected by the November 2010 withdrawal of the opioid analgesic propoxyphene might receive riskier prescriptions. To explore this, we compared drug receipts and outcomes among propoxyphene users before and aftermarket withdrawal. Study Design: Using OptumLabs data, we studied 3 populations: commercial, Medicare Advantage (MA) aged (age 65+ y) and MA disabled (age below 65 y) enrollees. The exposed enrollees received propoxyphene in the 3 months before market withdrawal (n=13, 622); historical controls (unexposed) received propoxyphene 1 year earlier (n=9971). Regression models estimated daily milligrams morphine equivalent (MME), daily prescription acetaminophen dose, potentially toxic acetaminophen doses, nonopioid prescription analgesics receipt, emergency room visits, and diagnosed falls, motor vehicle accidents, and hip fractures. Principal Findings: Aged MA enrollees illustrate the experience of all 3 populations examined. Following the market withdrawal, propoxyphene users in the exposed cohort experienced an abrupt decline of 69% in average daily MME, compared with a 14% decline in the unexposed. Opioids were discontinued by 34% of the exposed cohort and 18% of the unexposed. Tramadol and hydrocodone were the most common opioids substituted for propoxyphene. The proportion of each group receiving ≥4 g of prescription acetaminophen per day decreased from 12% to 2% in the exposed group but increased from 6% to 8% among the unexposed. Adverse events were rare and not significantly different in exposed versus unexposed groups. Conclusions: After propoxyphene market withdrawal, many individuals experienced abrupt discontinuation of opioids. Policymakers might consider supporting appropriate treatment transitions and monitoring responses following drug withdrawals. Abstract : Supplemental Digital Content is available in the text.